2003
DOI: 10.1021/ma025873n
|View full text |Cite
|
Sign up to set email alerts
|

Living ROMP of exo-Norbornene Esters Possessing PdII SCS Pincer Complexes or Diaminopyridines

Abstract: Isomerically pure exo-norbornene esters containing either a Pd II SCS pincer complex or a diaminopyridine unit were synthesized, polymerized, and copolymerized by ring-opening metathesis polymerization using a ruthenium initiator. All polymerizations are living under mild reaction conditions. A comparison between the pure exo monomers and the commonly employed 80:20 endo/exo mixtures was carried out. The exo-norbornene isomers exhibit significantly higher rates of propagation under milder conditions when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 34 publications
4
146
0
1
Order By: Relevance
“…In agreement with this work, previous studies of the ROMP of norbornene derivatives have also observed that endo isomers polymerize more slowly than their exo counterparts. 54,[60][61][62][63] The observed rate trends could be motivated by a combination of factors, including but not limited to pyridine coordination, olefin coordination, cycloaddition, and formation of a sixmembered chelate involving the ruthenium center and the esteror imide-functionalized chain end. 64 In order to deconvolute these potential contributions to khomo, we examined the mechanism of ROMP.…”
Section: Chart 1 Monomer Design For Ring-opening Metathesis Copolymementioning
confidence: 99%
“…In agreement with this work, previous studies of the ROMP of norbornene derivatives have also observed that endo isomers polymerize more slowly than their exo counterparts. 54,[60][61][62][63] The observed rate trends could be motivated by a combination of factors, including but not limited to pyridine coordination, olefin coordination, cycloaddition, and formation of a sixmembered chelate involving the ruthenium center and the esteror imide-functionalized chain end. 64 In order to deconvolute these potential contributions to khomo, we examined the mechanism of ROMP.…”
Section: Chart 1 Monomer Design For Ring-opening Metathesis Copolymementioning
confidence: 99%
“…Taking the values of activation parameters, it is assumed that there may exist active ruthenium in chelated form, which is proved in the following studies [28,36,45].…”
Section: Resultsmentioning
confidence: 99%
“…The simplest conceptual route to metal-containing polymers is the direct polymerization of metal-containing monomers. For the specific preparation of block copolymers, several notable routes of this sort have been developed, including the ring-opening polymerization of ferrocene derivatives, 47 the ring-opening metathesis polymerization of metal-coordinated norbornenes and Pd-pincer complexes, 48,49 and the chain polymerization of vinylferrocene. 6 In each case, a metal-containing monomer that is stable to the polymerization conditions is necessary; thus, either particularly stable monomers or mild polymerization conditions are required.…”
Section: Spatial Organization With Block Copolymersmentioning
confidence: 99%